2019
DOI: 10.3390/molecules24142588
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Accumulation of SPIONs under Arterial Flow Conditions: Effect of Serum and Red Blood Cells

Abstract: Magnetic drug targeting utilizes an external magnetic field to target superparamagnetic iron oxide nanoparticles (SPIONs) and their cargo to the diseased vasculature regions. In the arteries, the flow conditions affect the behavior of magnetic particles and the efficacy of their accumulation. In order to estimate the magnetic capture of SPIONs in more physiological-like settings, we previously established an ex vivo model based on human umbilical cord arteries. The artery model was employed in our present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…However, before starting experiments in animal models it is necessary to test how the SPION-loaded T cells behave under flow conditions and at a greater distance from the magnet. For this purpose, a setup like the one used by Hennig et al can be used [40]. Others also showed the ability of SPION-loaded T and NK cells to be magnetically attracted in a flow chamber in vitro [23,25].…”
Section: Magnetically Controllable T Cellsmentioning
confidence: 99%
“…However, before starting experiments in animal models it is necessary to test how the SPION-loaded T cells behave under flow conditions and at a greater distance from the magnet. For this purpose, a setup like the one used by Hennig et al can be used [40]. Others also showed the ability of SPION-loaded T and NK cells to be magnetically attracted in a flow chamber in vitro [23,25].…”
Section: Magnetically Controllable T Cellsmentioning
confidence: 99%
“…Hydrophobic particles are rapidly recognized and engulfed by the reticuloendothelial system [ 85 , 96 ]. Hennig et al [ 97 ] obtained lauric acid/BSA-coated and dextran-coated SPIONs with neutral surface charge, which remained colloidally stable without forming any aggregates. This feature is very important for cell endocytosis, as aggregates precipitate between cells in vitro and therefore give incorrect results.…”
Section: Reviewmentioning
confidence: 99%
“…They used two types of SPIONs, namely lauric acid/BSA-coated and dextran-coated SPIONs, and observed that when used in plasma or in whole blood, they produce clotting. However, both types of SPIONs cross the walls and accumulate in the tissue [ 97 ]. Wei et al used 80 nm PEG-coated SPIONs capped with epidermal growth factor and green fluorescent protein to target atherosclerotic plaques for MRI detection in vivo with good biocompatibility and good targeting resolution, showing that for this application retention time and dimension of the PEG-coated SPIONs were ideal [ 131 ].…”
Section: Reviewmentioning
confidence: 99%
“…In MDT, usually superparamagnetic iron oxide nanoparticles (SPIONs) are used as drug delivery carriers [6]. These particles consist of a small iron oxide core and, thus, are only composed of a single magnetic domain.…”
Section: Nanoparticlesmentioning
confidence: 99%